(untitled) (Web of Teachers: Inderscience Research, 2023)
In this article, the place of women in Hamza’s work is analyzed scientifically, philosophically, didactically, the image of women is highlighted as a special symbol, and its artistic and aesthetic features are analyzed, and an attempt is made to reveal them as examples.